2022
DOI: 10.1002/vetr.2080
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced ultrasound features of focal pancreatic lesions in dogs

Abstract: Background Contrast‐enhanced ultrasound (CEUS) features of pancreatic lesions are poorly reported in veterinary literature. Methods Qualitative and quantitative features of pancreatic benign (nodular hyperplasia [NH], cyst and abscess) and malignant (adenocarcinoma and insulinoma) lesions during B‐mode and CEUS examinations are described in 75 dogs. Results Adenocarcinomas (n = 23) had mixed echogenicity at B‐mode, and they were hypoenhancing or non‐enhancing at CEUS, with a non‐homogeneous and cystic enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In a study by Nagumo et al 2 including 44 dogs diagnosed with CA (six), CAC (12) and PHEO (26), the authors reported PHEO as having a significantly lower mean transit time compared to both CAC and CA. In other words, in their study, PHEO had a fast wash-in followed by a seemingly fast wash-out.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study by Nagumo et al 2 including 44 dogs diagnosed with CA (six), CAC (12) and PHEO (26), the authors reported PHEO as having a significantly lower mean transit time compared to both CAC and CA. In other words, in their study, PHEO had a fast wash-in followed by a seemingly fast wash-out.…”
Section: Discussionmentioning
confidence: 99%
“…The following qualitative CEUS features were evaluated during the wash-in phase 12,15 : (1) homogeneity of the lesion (homogeneous or non-homogeneous); (2) distribution of the contrast medium (diffused, peripheral or central); (3) hypoperfused areas (present or absent); (4) intralesional microcirculation (present or absent); (5) vascularisation pattern of microcirculation (centripetal, centrifugal, disordered or nodular). During the wash-in phase, vascular invasion was also evaluated.…”
Section: Qualitative and Quantitative Analysismentioning
confidence: 99%
See 3 more Smart Citations